Pengembangan Media Pembelajaran Fisika Berbantuan Screencast O Matic Berorientasi Peningkatan Minat dan Pemahaman Konsep - Lilis Jumiatin Afriani; Suji Ardianti; Syarif Fitriyanto; Fahmi Yahya (Indonesian Journal of Teacher Education, 2021)
An educator is required to learn and master technology as a solution to overcome the difficulties of students mastering the concepts presented. Based on the results of observations, one of the materials that requires a high understanding of concepts is static fluid. On the other hand, the online learning process during the COVID-19 pandemic greatly affects the interest and capture power of students. One way that can be done to overcome these conditions is to prepare physics learning media assisted by Screencast O Matic. The learning media developed were then designed and researched using a 4D development research model, namely the Define, Design, Develop and Disseminate. However, in practice this research is limited to the Develop stage, namely product development to limited trials. The instrument used is a questionnaire with a Likert scale measurement technique. The subjects of this study were 10 students of class XI MAN 2 Sumbawa who were selected using random sampling method. The results showed (a) Physics learning media assisted by Screencast O Matic was very feasible to be used in physics learning with a percentage of 83.82%; (b) The response of students to physics learning media assisted by Screencast O Matic is included in the very good category with a percentage of 88.05%. Based on these results, the physics learning media assisted by Screencast O Matic that has been developed is feasible to be used in learning.